2010
DOI: 10.1007/s00109-010-0701-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of histone deacetylase 7 (HDAC7) in cancer cell proliferation: regulation on c-Myc

Abstract: Histone deacetylases (HDACs) play fundamental roles in the epigenetic regulation of gene expression and contribute to the growth, differentiation, and apoptosis of cancer cells. Although HDACs are recognized to be closely related to cancer development and altered expression of certain HDACs is observed in tumor samples, the arcane characters of HDACs in tumorigenesis have not been fully illustrated. Herein, we report that HDAC7 is a crucial player in cancer cell proliferation. Knockdown of HDAC7 resulted in si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 34 publications
4
44
0
Order By: Relevance
“…HDAC5 strongly interacts with the tumour suppressor RUNX3 and induces its degradation through deacetylation 23. HDAC7 has been shown to protect from apoptosis by inhibiting c-Jun expression24 and contributes to carcinogenesis by transcriptional activation of c-Myc 25. However, little was known about expression and function of HDACs in IPF.…”
Section: Discussionmentioning
confidence: 99%
“…HDAC5 strongly interacts with the tumour suppressor RUNX3 and induces its degradation through deacetylation 23. HDAC7 has been shown to protect from apoptosis by inhibiting c-Jun expression24 and contributes to carcinogenesis by transcriptional activation of c-Myc 25. However, little was known about expression and function of HDACs in IPF.…”
Section: Discussionmentioning
confidence: 99%
“…This makes Class I HDACs promising targets for antitumor therapeutics. 6, 7, 8, 9, 10 As modifications in HDAC8 expression did not affect cancer cell proliferation 27, 28 and expression of Class I HDACs in CCA has not yet been studied, we set out to determine the expression of Class I HDACs (especially HDACs 1, 2 and 3) in CCA tissue.…”
Section: Discussionmentioning
confidence: 99%
“…5 Class I HDACs (1, 2, 3 and 8) have an important role in tumorigenesis and may be candidate targets for many cancer treatments. 6, 7, 8, 9, 10 Numerous reports indicate that Class I HDACs are overexpressed in many cancers and inhibit specific tumor suppressor genes, resulting in an aberrant epigenetic status compared with adjacent normal cells. 11, 12 Recently, studies showed that high levels of HDAC3 expression and activity had a critical role in cell epigenetic alterations associated with malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…These observations are compatible with the work of Zhu et al who showed that HDAC7 directly binds with c-Myc gene and that HDAC7 silencing decreased c-Myc mRNA highlighting the contribution of HDAC7 in cell proliferation and thus in tumor progression. 34 Moreover, HDAC10 have been shown to regulate Hsp90, 35 which stabilizes ZAP70, one of the most adverse prognosis factor in CLL patients. 36 These scores were able to clearly distinguish patients in three different subgroups, with median TFS ranging from 107 to 26 mo and median OS ranging from > 360 to 93 mo.…”
Section: Methodsmentioning
confidence: 99%